THE POSSIBLE PROSPECTS OF FENSPIRIDE USAGE IN PROPHYLAXIS AMONG SCHOOL-AGE SMOKERS - T. N. Kogevnikova; A. N. Protasenya (Вопросы современной педиатрии)
The results of epidemiological studies of recent years show that schoolchildren of middle and high classes can be considered as a potential audience for the prevention of the formation of chronic obstructive pulmonary disease, a disease that significantly affect the quality of life and life expectancy. Among the toxic components of tobacco smoke the most significant are polycyclic polycarbonates, oxides of nitrogen, oxides and dioxides of carbon. This study examined the content of carbon monoxide in exhaled air at smoking schoolchildren using the smokelayzer and assessed the possibility of using fenspiride in a complex health care interventions for tobacco smoking. The results of this study indicate a pronounced positive role of fenspiride in a complex of therapeutic measures in smoking schoolchildren.